2022
DOI: 10.3390/vaccines11010026
|View full text |Cite
|
Sign up to set email alerts
|

High Seroprevalence of Anti-SARS-CoV-2 IgM/IgG among Inhabitants of Sakaka City, Aljouf, Saudi Arabia

Abstract: (1) Backgrounds and Objectives: The global battle to contain the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) is still ongoing. This cross-sectional study aimed to detect the seroprevalence of anti-SARS-CoV-2 IgM/IgG among previously symptomatic/asymptomatic and vaccinated/unvaccinated inhabitants of Sakaka City, Aljouf, Saudi Arabia. (2) Methods: Blood samples of 400 participants were tested for the presence of anti-SARS-CoV-2 IgM/IgG using colloidal gold immuno-chromatography lateral flow imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
2
0
1
Order By: Relevance
“…Several studies have identified multiple factors associated with seropositivity, such as sex ( 20 , 21 ), age ( 20 , 21 ), obesity ( 20 ), exposure to more than one case among nonhousehold contacts ( 22 ), presence of multiple comorbidities ( 20 ), and previous performance of a PCR test ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified multiple factors associated with seropositivity, such as sex ( 20 , 21 ), age ( 20 , 21 ), obesity ( 20 ), exposure to more than one case among nonhousehold contacts ( 22 ), presence of multiple comorbidities ( 20 ), and previous performance of a PCR test ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the world is trying to counteract the bad effect of the coronavirus disease 2019 (COVID-19) pandemic, caused by SARS-CoV-2 (50, 51), on the communities, health systems, and economies (52,53). Anti-SARS-CoV-2 vaccination constitutes the most promising prevention and control measure (54,55). Recently, a few cases of herpes keratitis (approved by polymerase chain reaction [PCR]) due to the reactivation of HSV after receiving anti-SARS-CoV-2 mRNA vaccination were detected in Saudi Arabia (56), the United Kingdom (57), and Jordan (58).…”
Section: Discussionmentioning
confidence: 99%
“….А., Тотолян А.А. Характеристика набора реагентов «N-CoV-2-IgG PS» для количественного определения IgG человека к нуклеокапсидному белку SARS-CoV-2 // Инфекция и иммунитет 2022…”
unclassified